The CRAS-EAHFE study: Characteristics and prognosis of acute heart failure episodes with cardiorenal-anaemia syndrome at the emergency department. Issue 5 (August 2020) - Llauger, Lluis; Jacob, Javier; Herrero-Puente, Pablo; Aguirre, Alfons; Suñén-Cuquerella, Guillem; Corominas-Lasalle, Gerard; Llorens, Pere; Martín-Sánchez, Francisco J; Gil, Víctor; Roset, Alex; Ruibal, José C; Pérez-Durá, María J; et al.
Background: The coexistence of other comorbidities confers poor outcomes in patients with acute heart failure. Our aim was to determine the characteristics of patients with acute heart failure and cardiorenal anaemia syndrome and the relationship between renal dysfunction and anaemia, alone or combined as cardiorenal anaemia syndrome, on short-term outcomes. Methods: We analysed the Epidemiology of Acute Heart Failure in Emergency Departments registry (cohort of patients with acute heart failure in Spanish emergency departments). Renal dysfunction was defined by an estimated glomerular filtration rate <60 ml/min/m 2, anaemia by haemoglobin values <12/<13 g/dl in women/men, and cardiorenal anaemia syndrome as the presence of both. Comparisons were made according to cardiorenal-anaemia syndrome positive (CRAS+) with respect to the rest of patients (CRAS–) and according the presence of renal dysfunction (RD+) and anaemia (A+), (alone, RD+/A–, RD–/A+) or in combination (RD+/A+; i.e. CRAS+) with respect to patients without renal dysfunction and anaemia (RD–/A–). The primary outcome was 30-day mortality, and the secondary outcomes were need for admission, prolonged hospitalisation (>10 days), in-hospital mortality during the index event, and reconsultation and the combination of 30-day post-discharge reconsultation/death. These short-term outcomes were compared and adjusted for differences among groups. Results: Of the 13, 307 patients analysed, CRAS+ (36.4%) was associated with older age, multiple comorbidities, chronic use of loop diuretics, oedemas and hypotension. The 30-day mortality in CRAS+ was greater than in CRAS– (hazard ratio = 1.46, 95% confidence interval = 1.26–1.68) and RD–/A– (hazard ratio = 1.83, 95% confidence interval = 1.46–2.28) control groups. The mortality level was also higher in RD+/A– (hazard ratio = 1.40, 95% confidence interval = 1.10–1.78) and higher, but not statistically significant, in RD–/A+ (hazard ratio = 1.28, 95% confidence interval = 0.99–1.63) with respect to RD–/A–. All of the secondary outcomes, when related to CRAS– and RD–/A– control groups, were worse for CRAS+ and to a lesser extent, RD+/A–, being more rarely observed in RD–/A+. Conclusions: Cardiorenal anaemia syndrome in acute heart failure is related to greater mortality and worse short-term outcomes, and the impact of renal dysfunction and anaemia seems to be additive.